KANDUNGAN NUTRISI TEPUNG DAUN KANGKUNG AIR (Ipomoea aquatic Forssk) YANG DI FERMENTASI EM-4 SEBAGAI ALTERNATIF BAHAN PAKAN UNGGAS - Danang Biyatmoko; Purniati Purniati; Nursyam Andi Syarifuddin (ZIRAA'AH MAJALAH ILMIAH PERTANIAN, 2019)
This study aims to analyze the nutrient content of fermented water spinach leaf flour on the content of dry matter, organic matter, and crude protein with different EM-4 levels and their economic prices as an alternative to poultry feed ingredients. The research method used was a completely randomized design (RAL), with five treatments and five replications, where each replication consisted of one container of fermented containers. The variables observed were dry matter, organic matter, and crude protein. The data obtained were analyzed using a variety of analyzes where previously the data homogeneity test was carried out. If the treatment shows a significant and very significant effect, then it will be followed by Duncan's multiple range test. The results showed that the nutrient content of water spinach fermented leaf flour on the content of dry matter and organic matter decreased, while the crude protein content increased, so that it showed very different values (p <0.01) the economic value of making fermented water spinach leaf flour the best is 0.4% EM-4 is equal to Rp.420, -